The epidemiology of Chronic Non-Communicable Diseases (NCDS) and NCD risk factors in adolescents & youth living with HIV in Cape Town, South Africa - Kamkuemah, Monika (Department of Public Health and Family Medicine, 2022)
Introduction: South Africa, like many other low- and middle-income countries (LMIC), is currently undergoing an epidemiological transition with a growing burden of noncommunicable diseases (NCDs) co-occurring with an existent burden of infectious diseases like human immunodeficiency virus (HIV). South Africa continues to have the biggest HIV epidemic globally, and adolescents and young people, especially young women, bear a disproportionate burden of HIV in the country. Adolescents and youth living with HIV (AYLHIV) face an elevated NCD risk resulting from chronic immune activation, psychosocial factors and the complications of long-term antiretroviral therapy (ART). However, there is data paucity on the intersection of NCDs and HIV in adolescents in South Africa and Africa. This thesis aims to contribute to the limited evidence base in LMIC settings by investigating NCD multimorbidity and risk factors in AYLHIV within a context of epidemiological transition and urbanisation. Objectives: This aim is achieved by fulfilling the following research objectives: 1. To investigate the extent to which NCD comorbidity (prevention, screening and management) is incorporated within existing adolescent HIV primary healthcare services in Cape Town, South Africa. 2. To estimate the prevalence of common NCDs and their known cardiometabolic, respiratory and behavioural risk factors in AYLHIV residing in peri-urban Cape Town. 3. To determine individual, household, social and neighbourhood level factors associated with obesity in AYLHIV. Methods: I conducted a narrative literature review to inform the development of a conceptual framework for investigating the intersection of adolescence developmental theory with NCDs and HIV. The emergent concepts were explored from an over-arching socioecological viewpoint, drawing on life course epidemiology and epidemiological transition theories. I conducted a cross-sectional quantitative study in nine primary care facilities across peri-urban Cape Town. The study was conducted in two parts. The first part of the study was comprised of data collected from 491 medical records of AYLHIV accessing HIV care in these facilities. The second part of the study sought to investigate the epidemiology of NCDs and NCD risk factors and to assess multilevel factors associated with abdominal obesity (the primary outcome). I recruited 176 eligible AYLHIV to participate in the study with primary data (on NCDs and NCD risk factors) collected from 92 participants during routine clinic visits between March and December 2019. Results: The findings from the 491 patient medical records reviewed demonstrated limited attention to NCD comorbidity prevention, screening and treatment within adolescent HIV primary care services. Only 62% of patient folders had documented anthropometric measurements, 59% had documented blood pressure measurements, and less than 11% of patient folders reviewed had any NCD health promotion documented. Among the 92 participants recruited for primary data collection, 76% were female. More than a quarter (27%) were not in education, employment or training; 70% lived in food-insecure households, and 44% were multidimensionally poor. At the individual level, a high prevalence of NCDs was found, particularly elevated blood pressure and hypertension (20% and 5% respectively), overweight/obesity (36%), central obesity (37%), and depressive symptoms (43%). With respect to NCD risk factors, 69% reported engaging in sufficient physical activity (79% of males and 66% of females), and 49% reported three or more hours of sedentary behaviour per day. However, unhealthy dietary practices were common, with only 27% eating fresh fruit, 52% eating vegetables and 33% eating whole grains daily. On the other hand, 29% drank sugar-sweetened beverages, and 33% ate sweets and cakes daily, while 42% skipped breakfast regularly. Furthermore, nutritional knowledge was low, especially with respect to healthy food choices and dietdisease relationships. Risky behaviours were also prevalent with 30% current smokers (48% males and 25% females) and 41% alcohol use in the past month (58% males versus 36% females), with binge drinking most commonly reported in the youngest age group < 18 years (55%). Significantly more malesreported lifetime use of any illicitsubstances(53% versus 30% for females), with cannabis the most frequently reported substance used (23% lifetime prevalence). Beyond individual-level risk factors, household-level factors were also explored. More than half (58%) reported the death of one or both parents, while 47% reported a biological parent as their primary caregiver. Parental level factors were largely positive, with participants reporting high levels of positive parenting and parental supervision. However, 35% lived in informal dwellings, 38% did not have access to piped water inside their dwelling and 62% experienced thermal discomfort in winter. Community experiences revealed a mixed picture, with 61% of participants exposed to high levels of community violence, while participants largely reported high neighbourhood belonging and low levels of stigma. Multilevel regression was conducted to investigate the factors associated with abdominal obesity at different socio-ecological levels. All models were adjusted for sex and age. Statistically significant individual-level risk factors that were associated with higher odds of abdominal obesity were skipping breakfast (OR= 5.42; 95% confidence interval (CI): 1.32 – 22.25) and absence from school or work (OR= 3.06; 95% CI: 1.11 – 8.40), while daily whole grain consumption (OR= 0.20; 95% CI: 0.05 – 0.71) and weekly moderate-intensity physical activity (OR = 0.24; 95% CI: 0.06 – 0.92) were associated with lower odds of abdominal obesity. At the household- and community levels, experiencing thermal discomfort was associated with increased odds of obesity (OR= 4.42; 95% CI: 1.43 – 13.73), while higher anticipated stigma was associated with reduced odds of obesity (OR= 0.58; 95% CI: 0.33 – 1.00). The features of the built and food environment that were associated with reduced odds of abdominal obesity in AYLHIV were land-use mix diversity (OR= 0.52; 95% CI: 0.27 – 0.97), access to recreational places (OR= 0.37; 95% CI: 0.18 – 0.74), higher perceived pedestrian and traffic safety (OR= 0.20; 95% CI: 0.05 – 0.80), and having a non-fast-food restaurant within walking distance (OR= 0.30; 95% CI: 0.10 – 0.93). Conclusion: These results indicate an existent burden of NCDs and NCD risk factors in urban AYLHIV. Beyond the NCD risk attributable to HIV and ART, these multiple risk factors coupled with early initiation of high-risk behaviours like smoking and harmful alcohol use further increase NCD risk. Despite high NCD comorbidity and risk, evidence shows little to no integration of health services and limited responsiveness with regards to NCD health promotion. These findings underscore a missed opportunity in multimorbidity prevention. Overall, these findings highlight the need for a comprehensive, integrated approach for AYLHIV to both prevent and manage NCD multimorbidity within primary care. This integrated approach should include mental health assessment and screening for weight status, abdominal obesity and blood pressure to identify comorbid NCDs early and intervene to improve NCD outcomes. Additionally, risk factor screening should be incorporated into HIV care to prevent NCD multimorbidity. Screening should include early identification of the most common NCD risk factors (insufficient physical activity, poor dietary practices, smoking, alcohol use and binge drinking, particularly in male adolescents and younger age groups). These findings also highlight the need for intervention at various levels of the socio-ecological framework through multisectoral interventions in the social and built environments. Finally, this thesis contributes an evidence base to inform the development of integrated and intersectoral models of care to address the colliding epidemics of HIV and NCDs in young people in LMIC settings.